State, acceleration of technological innovations, restrictions on rights and profitability - Silva, Maria Lucia Lopes da (Argumentum, 2024)
This article deals with the promotion of technological innovations as an essential element of contemporary capitalist accumulation, highlighting the role of the State in stimulating this process through financial investment and intensive use of digital technologies in public services. It highlights the relationship of this use with restrictions on access to rights, especially social security rights, and with capitalist profitability. It presents the results of bibliographic review and of post-doctoral documentary research on the subject. The concludes that the intensive use of digital information and communication technologies in public services has favoured capitalist profitability and contributed to the restriction of access to rights.